If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5y + 30 = 3x Reorder the terms: 30 + 5y = 3x Solving 30 + 5y = 3x Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-30' to each side of the equation. 30 + -30 + 5y = -30 + 3x Combine like terms: 30 + -30 = 0 0 + 5y = -30 + 3x 5y = -30 + 3x Divide each side by '5'. y = -6 + 0.6x Simplifying y = -6 + 0.6x
| 3x-6/4=12 | | v^2-2v-5=0 | | 545/5 | | y/0.5=-6 | | 2x+(-3)=9 | | log(x+6)-log(6)=log(12) | | ln(3x)=x-4 | | y/.5=-6 | | 2ln(x+4)=4 | | -(7-8A)-(2+7A)-27=-(3-7A)+(-A)+2 | | 2(2x-i)-4x-6x= | | 5*3/5x-5*6 | | 9x^4-18x^2+5=0 | | 4r^3=72 | | 1/2x2/7= | | 4c=54 | | 1.3x+2.1=5.7 | | 24+4b=8 | | 17.64*8= | | 7(8)=56 | | 81x^2+1=101 | | a=3*w | | (-7xz^5/y)^3 | | -4(3+4n-3m)= | | -4.5-1.3+4.5= | | Log(x+4)+log(4x+3)=2log(2x) | | 2250/2= | | 14m-3n-2m+5n= | | 10*15*15= | | f=bexp(-a*x) | | x+2y=4y+3 | | -4/7u=-16 |